Colonic metastasis from primary lung adenocarcinoma: a case report and review of the literature - Thomas, Kelly; Mirza, Zuheir; Coppola, Domenico; Friedman, Mark (AME Medical Journal, 2017)
A 64-year-old man presented to his primary care physician with hemoptysis. A CT scan revealed a mass in the right hilum of the lung and a fine needle aspiration of a left supraclavicular lymph node confirmed adenocarcinoma of the lung. To determine the stage of cancer, a full body PET/CT scan was performed. This suggested metastasis to the left femur, pancreas and colon. Colonoscopy showed an irregular area of mucosa of the splenic flexure. Biopsies revealed an invasive adenocarcinoma. Immunohistochemical analysis showed the tumor positive for TTF-1, napsin and CK7 and negative for CK20, supporting a metastasis from a lung adenocarcinoma. Upon review of current literature, only five cases of lung adenocarcinoma metastasizing to the colon have been documented.